The Effects of Oxygen and Treatments in Hypoxic Conditions in SH-SY5Y Cells. Issue 4 (October 2018) - Cho, Young-Duck; Choi, Sung-Hyuk; Yoon, Young-Hoon; Kim, Jung-Youn; Park, Sung-Jun; Lim, Chae-Seung
Abstract : ABSTRACT: Many patients are admitted to the emergency department due to trauma. Patients with massive hemorrhage and respiratory failure can fall into hypovolemic shock. Thereafter, oxygen is an essential part of the treatment of trauma patients, but the mechanisms of its effects in the management of trauma patients remain unknown. Therefore, we conducted an experiment to apply hypoxia, hyperoxia, and other treatment with the goal of decreasing hypoxic neuronal cells damage, as reflected by cell survival, apoptosis, hydrogen peroxide (H2 O2 ) production, and hypoxia-inducible factor 1α (HIF) expression in SH-SY5Y cells. Under hypoxic insults, cell survival percentages decreased and apoptosis was seen with increased necrotic cell death. High-pressure oxygen (80% O2 ) had no effect compared with normal-pressure oxygen (20% O2 ). After exposure to hypoxia, H2 O2 production and levels of HIF significantly increased compared with normoxia. However, when pentoxifylline (PTX), steroid, and hypertonic saline (HTS) were added after exposure to hypoxic conditions, the production of H2 O2 and HIF levels significantly decreased in the groups treated with PTX and HTS. That is, the neuroprotective effect of PTX and HTS alleviated the impacts of hypoxic insulted on neuronal cells.